Economic Status of the Tourism Sector during the COVID 19 Pandemic at Lake Toba Parapat - Raisha Ghadati Raudina; Anthoni Veery Mardianta (International Journal of Architecture and Urbanism, 2022)
Parapat is the main gateway to Samosir Island and is often referred to as Parapat Tourism City. The presence of Lake Toba with its natural beauty makes the surrounding area a priority object and tourist attraction (ODTW) in North Sumatra. Currently, the Lake Toba area is designated as the National Tourist Destination (DPU) in North Sumatra. At the beginning of 2020, the world was shaken by the presence of the Covid-19 virus outbreak. The Indonesian government has also acted to contain the spread of Covid-19 by implementing the policy "Enforcement of Community Activities Restrictions Enforcement (PPKM)". The existence of these social restrictions has led to the stagnation of the tourism industry. The state of Indonesia's tourism economy, especially Parapat, remains volatile due to the Covid-19 pandemic. The purpose of this study is to investigate the economic situation of the tourist destinations of Parapat in the Covid-19 pandemic. This study uses a qualitative study with a descriptive approach. The data collection techniques used in this study include observational studies and literature studies. Looking at the economy of the tourism sector based on the WTO's Tourism Baseline Index for tourism destinations, there are three parameters: business investment in tourism, income from the tourism sector, and public spending. According to the survey, in 2020, the Covid-19 pandemic and the government's implementation of the Community Activities Restrictions Enforcement (PPKM) caused the decline of various economic sectors in the tourism industry